Editorial to the special issue on applications of complexity for resilient organizations, management and innovation systems - Silvano Cincotti; Ilaria Giannoccaro; Cristina Ponsiglione; Linda Ponta; Andreas Pyka (Journal of Economic Interaction and Coordination, 2024)
Abstract Welcome to the Special Issue on Applications of Complexity for Resilient Organizations, Management, and Innovation Systems. This Special Issue includes six articles highlighting how complexity science and complex systems approaches can be employed to study resilient aspects in organizations, management and innovation systems. Nowadays, governments, policy-makers, managers, firms, and organizations are requested to face challenges with possible and unpredictable disruptive events always more and more interconnected. Complexity science and complex systems approaches applied to economic and managerial systems allow to model the endogenous dynamics of a system as a whole and composed~of heterogeneous interacting agents from the bottom up. Such models open the opportunity for a dynamic and systemic approach to investigate and improve the resilience of organizations and innovation systems. It is crucial to remark that both scholars and decision-makers collaborated on the Special Issue to better understand the advantages of using a systemic approach (i.e., complexity science and complex systems approaches) in areas where such methodologies have not been considered so far, i.e., organization, innovation, and management. To aid in this endeavor, the papers included in the Special Issue investigate different conceptual and methodological aspects applied in different contexts and open a new vista on the opportunity offered by complexity science and complex systems approaches to face research and professional questions in the areas of organization, management, and innovation.
Keywords: 330; Complexity; Resilience; Organization; Management; Innovation systems